Topic familiarization and vocabulary introduction in second language reading / Mohsen Pornour - Pornour, Mohsen (2012)
Although the field of second language teaching and learning has witnessed an enormous amount of research on reading skills, in general, and on topic familiarity and vocabulary teaching/learning, in particular, almost no attention has been paid to the teacher‟s role in topic familiarization and vocabulary introduction. In an attempt to fill this gap, and in an explanatory mixed methods design, the present study investigated the effects of the teacher‟s intervention in an L2 reading class by comparing the applicability of written topic familiarization with the effectiveness of teacher-directed topic familiarization in students‟ performance of comprehension tests. Furthermore, the adequacy of students‟ dictionary use was compared with the efficacy of teacher‟s instruction of vocabulary in enhancing students‟ performance of vocabulary tests. Finally, students‟ perceptions of teacher-directed versus written topic familiarization as well as their perceptions of dictionary use versus teacher‟s vocabulary instruction were investigated. For this purpose, 73 undergraduate students studying English as an L2 in an Iranian university were homogenized into two groups of A (No Teacher) and B (Teacher) based on their proficiency results of the Oxford Quick Placement Test. The participants experienced four treatments, Group B with the presence and Group A without the presence of a teacher. Both groups were provided with pre-reading tasks. For Group A, the activities were in the form of scripts of explanations, including brainstorming questions, an introductory paragraph intended to familiarize the participants with the reading topics, and a list of the key words. Group A students were asked to use dictionaries for vocabulary meaning. However, the pre-reading activities in Group B were teacher-directed. The participants in this group were provided with the same information as that of Group A to ensure consistency, but through the teacher, and were not allowed dictionaries as the teacher taught them the key words. Each time the participants read a passage of unfamiliar topic, after which they were tested on comprehension recalls and multiple-choice questions, and vocabulary MCQs. The participants also completed a Likert-scale perception questionnaire at the end of the study, and 23 students were interviewed. Results of independent-samples t-tests did not indicate any significant difference between teacher-directed and written topic familiarization although paired t-tests showed that both of the approaches by themselves were effective on students‟ comprehension tests results. However, teacher‟s vocabulary instruction was confirmed to be significantly more effective than students‟ dictionary use, and paired t-tests once again showed that each method per se caused significant results in students‟ vocabulary tests performance. Results of the perception questionnaire triangulated with interview responses confirmed that the students thought teacher-directed topic familiarization and written background knowledge activities were equally effective, which agreed with their comprehension tests results. However, most of the participants thought that there was no significant difference between students‟ dictionary use and teacher‟s instruction of vocabulary, which contradicted their vocabulary tests results. Only some students perceived teacher‟s instruction as more effective than dictionary usage. This might imply that students‟ perceptions are not always very reliable for decision-making in L2 reading. Furthermore, the study is believed to have useful implications for students, teachers and educators as well as authors and publishers.